Identifying community-based emergency response for toxic gas release using the fuzzy Delphi method - Ahmad, Noor Afzan; Kidam, Kamarizan; Mohsin, Rahmat (AIP conference proceedings, 2023)
Effective community-based emergency response requires a concerted approach to the management of emergency response. An effective and resilient community must have partnerships with local governments, organisations, citizens, and industries to enhance the response to toxic gas releases and lessen their impacts. Without these partnerships, communities will continue to be vulnerable to potential hazardous materials disasters. The aim of this study is to provide a conceptual framework for community-based emergency response to toxic gas releases. This study identified four constructs for emergency response: coordination, collaboration, communication, and capability as the moderators that can influence the community to produce an effective emergency response framework. To explore the elements of community-based emergency response, this study used document analysis, interviews, and the questionnaire, validated by subject matter expert (SME) in the field of emergency response to toxic gas releases. The data gathered was analysed using Fuzzy Delphi Method (FDM). This study provides a new insight to students, researchers, and scholars regarding the need to adopt the emergency response elements for the community. Thus, they will be able to apply emergency management knowledge in the various elements of emergency response.